BAGIAN WARIS BAGI JANDA DALAM HUKUM KEWARISAN ISLAM DAN KOMPILASI HUKUM ISLAM - Dwi Wulandari (Postgraduate State Islamic Institute (IAIN) Metro, 2020)
During this time, science Mawaris only studied in the Islamic legal literature, which is still general science. The distribution of inheritance follows what has been mentioned in the Qur'an and al-Sunnah and there are additions from the ijtihad results of the Companions in the Arab countries. The structure of Indonesian people's life which is different from the Arab community, makes the Islamic Inheritance Law appear rigid and difficult when applied in Indonesia, so that many Muslims in Indonesia prefer adat inheritance law. Through the literature study method, writing examines as well as disseminates information related to the Compilation of Islamic Law that is used to implement Islamic inheritance law in Indonesia that is not widely known by the public. Indonesian ’ulama who have studied mawaris, are trying to formulate Islamic inheritance law by considering the conditions of Indonesian society, so that this Islamic inheritance law can be accepted by Indonesian Muslims. The efforts of the 'ulama bore fruit with the birth of the Compilation of Islamic Law, even though its status is still the President's instruction and has not been made official as a law. But it has been applied in the Religious Courts and is disseminated and reviewed in tertiary institutions.